India's land forces structural imperatives - Singh, Jaspal
The author identifies the Land Forces - the Army, and the Para-Military Forces maintained under the Ministry of Home Affairs and takes an objective view for their optimal employment. This is a bold exposition of gaping holes in India's security systems that need to be addressed and refined.